2021
DOI: 10.1093/jn/nxab187
|View full text |Cite
|
Sign up to set email alerts
|

Avocado Consumption, Abdominal Adiposity, and Oral Glucose Tolerance Among Persons with Overweight and Obesity

Abstract: Background Although intake of Hass avocado has been cross-sectionally linked to lower abdominal obesity, knowledge of the effects of avocado consumption on abdominal adiposity and glycemic outcomes remains limited. Objective The effects of avocado consumption on abdominal adiposity, insulin resistance, oral-glucose-tolerance test (OGTT), and estimated β-cell function were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…This study presents the first comprehensive review of Hass avocado clinical trials, observational studies, and biological mechanisms. We found that the Hass avocado has four major health benefits (Figure 17): (1) cardiovascular health [12][13][14][15][16][17][18][19][20][21][22]; (2), weight control [23][24][25][26][27][28][29][30]; (3) cognitive health [18,31,33]; and (4) colonic microbiota health [26,34]. We also found that four nutritional features were primarily responsible for all the major avocado health benefits: (1) high unsaturated to saturated fat ratio [7]; (2) viscous and prebiotic fiber [2,7]; (3) a relatively low energy density of 1.6 kcal/g [7]; and (4) high carotenoid bioavailability [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study presents the first comprehensive review of Hass avocado clinical trials, observational studies, and biological mechanisms. We found that the Hass avocado has four major health benefits (Figure 17): (1) cardiovascular health [12][13][14][15][16][17][18][19][20][21][22]; (2), weight control [23][24][25][26][27][28][29][30]; (3) cognitive health [18,31,33]; and (4) colonic microbiota health [26,34]. We also found that four nutritional features were primarily responsible for all the major avocado health benefits: (1) high unsaturated to saturated fat ratio [7]; (2) viscous and prebiotic fiber [2,7]; (3) a relatively low energy density of 1.6 kcal/g [7]; and (4) high carotenoid bioavailability [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Four observational and five clinical studies evaluated the effects of Hass avocados on weight management or hunger and satiety [4,[23][24][25][26][27][28][29][30][31][32]. Current dietary guidelines recommend the consumption of an adequate intake of a variety of fresh fruits and vegetables to help maintain and achieve a healthy weight through reducing eating rate, lowering the total dietary energy density (ED), and increasing fiber intake by displacing other foods and snacks that are moderate to high in ED and low in fiber [1,31].…”
Section: Body Weight Managementmentioning
confidence: 99%
See 3 more Smart Citations